Hibridisasi Sintesis dan Uji Aktivitas Antikanker Turunan Baru Asam Karboksilat secara In-Silico dan In-Vitro - Asyfariatus Zulfa Azhar; Warsito Warsito; Arie Srihardyastutie (Jurnal Penelitian Pendidikan IPA, 2023)
Design of new compounds as active ingredients of drugs must be selective and efficient to achieve therapeutic efficacy and minimize resulting side effects. Hybridization synthesis approaches using major components of essential oils can reliably generate new molecules that are superior as active ingredients of anti-cancer drugs due to their cytotoxic properties. This study synthesized a hybrid molecule of citronellyl salicylate by an esterification reaction using Steglich and Fisher method under ultrasonic assistance. The Steglich esterification is more efficient in producing citronellyl salicylate during 30 minutes reaction, yield 12.45%. Analysis of the synthesized product by FTIR is characterized by the presence of typical absorptions of the ester group at á¿¡ 1650 cm-1 and 1270 cm-1, while LC ESI-MS shows m/z 294 is indicated [M+NH4]+. Anticancer activity was tested in-silico for protein receptors MMP-9, MMP-2, Cyclin-A, p53, and BAK using Molecular Docking Pyrx 9.0 and the highest activity was shown binding affinity value -8.4 kcal/mol for the MMP-9 protein receptor.Â Similarly, the results of the in vitro activity assay of citronellyl salicylate to 4T1 breast cancer cells showed that the morphology of cancer cells was damaged and the viability of cancer cells was lower than that of normal cells